ANALYZING THE STRATEGY AFFECTING SURVIVAL OF PONDOK TETERUSAN RESTAURANT - Kalumata, Gabriella F. M.; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2019)
Abstract: Business in modern era keeps evolving in order to meet the standard of customers thus creating certain types of criteria and even new barriers for new businesses in modern era. This forces the companies create strategies in order to survive the competition. This study aims to analyse the strategy of Pondok Teterusan restaurant to survive in the competition of grilled fish business. This study used qualitative method with purposive sampling. The sample of this study is owner and eight customers of Pondok Teterusan restaurant. The data collected by doing deep interview. The result shows that there is no special strategy implemented by the restaurant to survive within the industry. Customer review helps the restaurant to evaluate their performance, product differentiation makes the restaurant has variant menu and the restaurant has strategic location that affecting the survival of the restaurant. The restaurant can make the customer satisfaction or review board to collect the customer feedback. The owner also have to give more attention to the area of the restaurant to make the customer feel comfortable.Â Keywords: restaurant, strategy